2019
DOI: 10.1371/journal.pone.0218176
|View full text |Cite
|
Sign up to set email alerts
|

Is gene editing an acceptable alternative to castration in pigs?

Abstract: Male piglets are commonly castrated to eliminate the risk of boar taint. Surgical castration is the commonly used procedure and is known to induce pain. Gene modification targeted at eliminating boar taint in male pigs has been proposed as a possible alternative to surgical castration. The aims of this study were to explore public acceptability of this biotechnology using a mixed methods approach. Quantitative data to assess acceptability of 570 participants from southern Brazil were analysed with multinomial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 57 publications
(68 reference statements)
2
36
0
1
Order By: Relevance
“…This example represents a potential approach for reducing physical dehorning in dairy cattle without loss of productivity. As mentioned, the use of CRISPR to produce germline ablated male pigs has been proposed [50], and even thought this remains to be proven, it would offer new opportunities to finish with surgical castration in pigs [60,61]. Avoiding these practices in animal husbandry may encourage public support of genome-edited animals for food chain production.…”
Section: Improving Animal Welfarementioning
confidence: 99%
“…This example represents a potential approach for reducing physical dehorning in dairy cattle without loss of productivity. As mentioned, the use of CRISPR to produce germline ablated male pigs has been proposed [50], and even thought this remains to be proven, it would offer new opportunities to finish with surgical castration in pigs [60,61]. Avoiding these practices in animal husbandry may encourage public support of genome-edited animals for food chain production.…”
Section: Improving Animal Welfarementioning
confidence: 99%
“…Although some studies indicated that consumers in Europe have positive attitudes towards immunocastration [ 31 , 32 , 56 ], a widely reported limitation for adoption of this method is producers’ and industry stakeholders’ concern regarding consumer acceptance [ 17 , 20 , 23 , 48 ]. Indeed, health and safety aspects are the animal production traits that consumers in different parts of the world perceive as most important when assessing alternatives to pig castration [ 30 , 33 , 48 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to maintain its’ social license, the livestock industry must regard the values of citizens and consumers. Although citizens in general are unaware of the husbandry practices and technologies used in animal production, when asked about surgical castration of pigs without anesthesia, most classify these practices as detrimental to animal welfare [ 30 , 31 , 32 , 33 ]. Housing and management practices that are highly prevalent in intensive pig farming such as confinement, feeding practices that leave animals hungry for most of the day, and painful mutilations have become highly contentious [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of surveys of public opinion are starting to emerge [52][53][54] . These show general support for application of the technology, with a parallel cry for more information so that informed opinions can be developed [55] . Recognized as a topic of public interest, the Nuffield Council on Bioethics (UK) is currently preparing a report on 'Genome Editing and Farmed Animals' which will provide a yardstick on the ethical aspect of this technology in livestock.…”
Section: Summary and Future Perspectivementioning
confidence: 79%